Hubungan Daya Ledak Otot Lengan dan Koordinasi Mata-Tangan terhadap Ketepatan Servis Atas Bola Voli Siswa Ekstrakurikuler di SMPN 14 Pontianak - Suri Dwi Ananda; Fitriana Puspa Hidasari; Doni Pranata; Victor G Simanjuntak; Witri Suwanto (Universitas Negeri Semarang, 2024)
This study aims to determine how arm muscle explosive power and hand-eye coordination correlate with the accuracy of overhead serves. This research is of a correlational type. The sampling technique used is total sampling. The overhand medicine ball throw test was used to examine eye-hand coordination, and data on arm muscle explosiveness was retrieved from that test. An AAHPER service target test instrument is used to measure the upper service accuracy test. Product moment correlation and subsequent multiple correlation analyses were performed on the data. According to the study's findings, 1) SMPN 14 Pontianak volleyball extracurricular students' r-calculations (0.744 ≥ 0.381) demonstrated a strong association between their arm muscles' explosive strength and the accuracy of their service. 2) The r-value (0.886 ≥ 0.381) and the r-table (0.986 ≥ 0.381) showed a significant correlation between eye-hand coordination and the precision of service for SMPN 14 Pontianak's extracurricular volleyball players. The accuracy of service for extracurricular volleyball players at SMPN 14 Pontianak is significantly correlated with their arm muscle explosiveness and hand-eye coordination (r = 0.90, extremely high correlation category).